Music teacher and researcher: narrative reflexivity from behind the scenes of a research (Orfeu, 2022)
This paper presents my narrative about some experiences I had in the process of my doctorade research, developed within a Pedagogy course at a public university. The aim is to understand how narrative reflexivity contributes to the researcher education process. I do not intend to reveal the truth the truth about the facts, but to present the autobiographical narrative according to Passeggi (2016, 2021), as a methodological option to rescue some experiences I lived with the students who participated of the research, and the meanings I gave them during and after the study process in the subject. Methodologically, I narrate the research trails, the field diary records, the video transcripts or the memory device to understand the knowledge and wisdoms woven in this production. I conclude that to become a researcher it was necessary to learn to be in silence, to sit alone for hours and hours in search of reasoning, questions, answers or even originality.
Keywords: music; training; research; narrative reflexivity